How do elite female team sport athletes experience mental fatigue? Comparison between international competition, training and preparation camps. - Russell, S.; Jenkins, D. G.; Halson, S. L.; Juliff, L. E.; Kelly, V. G. (European Journal of Sport Science, 2022)
Mental fatigue has been shown to negatively influence physical, technical and tactical aspects of sporting performance. However, mental fatigue is not routinely monitored or managed in elite sport and it is not clear whether mental fatigue occurs and/or changes across the varied contextual demands experienced by elite athletes in training, preparation and competition. This study explored self-report measures of mental fatigue across eight training camps and six competition periods (two benchmark tournaments and four international test series) with international netballers (n = 22, 25.9 ± 2.7y) during the 2018-2019 representative period. Mental fatigue was higher during training camps (p < 0.001; 3.20 [3.12, 3.27]) and preparation camps (p < 0.05; 3.27 [3.19, 3.34]) compared to the competition periods (3.49 [3.44, 3.55]). Significant within-group differences were also identified between individual preparation camps and competition subsets. Higher mental fatigue was reported during the preparation camp for international test series 2 comparative to the preparation camp for benchmark tournament 1 (p = 0.047). For individual competitions; greater mental fatigue was found during the international test series 3 competition in comparison to both the benchmark tournament 1 (p <0.001) and international test series 1 (p = 0.020) competition periods. International representative netballers experience differing levels of mental fatigue across training and preparation camps and competition periods. Practitioners should be aware that athletes report instances of elevated mental fatigue across camps, and competition. Mental fatigue is not limited to competition and thus is recommended to be monitored during periods of training and preparation for competition.